MENUMBUHKAN LOYALITAS PENGUNJUNG KULINER WISATA DI BANDUNG - Etik Ipda Riyani, Etik Ipda Riyani; Devi Ayuni, Devi Ayuni; Andy Mulyana, Andy Mulyana (Fakultas Ekonomi UM Metro, 1978)
The purpose of this study is to analyze the interrelation between service quality, perceived value, satisfaction, trust and loyalty. The population in this study is a visitors culinary tourism in Bandung. This study uses PLS (Partial Least Square) with several variables of service quality, perceived value, satisfaction, trust, and loyalty. Data obtained by distributing questionnaires to the respondents. The number of samples used as objects of research of 270 respondents. The results showed that the service quality rendered by providers in Bandung culinary significant effect on the perceived value. Service quality provided by the culinary providers in Bandung do not directly affect the respondents satisfaction, but the indirect effect through perceived value of the respondent. This is because in order to achieve satisfaction, respondents had to feel the perceived value of culinary services provider in Bandung. Perceived value significantly influence respondents satisfaction and loyalty. Satisfaction significant impact on the trust and loyalty of respondents. Trust significant effect on loyalty respondents. Â Keywords: service quality, perceived value, satisfaction, trust, loyalty